Essay on the constituent function of constitutional courts of french-speaking sub-saharan Africa : examples of Benin, Côte d'Ivoire, Gabon, Niger and Senegal - (:unkn) unknown (My University, 2021)
The democratic renewal of the 1990s, beyond the re-establishment of a multi-party system and individual rights, led to the adoption of new constitutions south of the Sahara. In the former French colonies, which are now independent, there has been a reconfiguration of jurisdictional power. Either detached from the ordinary courts or placed outside the judiciary, the new autonomous constitutional courts were entrusted, beyond the classic control of constitutionality, with attributions hitherto unheard of in French-speaking black Africa, and even in the former metropolis. As official interpreters of the constitution and regulators of institutions, most African constitutional judges are thus empowered to exercise a constituent function, i.e. to revise the fundamental law.In a part of the world where nominal constitutions proliferated in the past, these extraordinary powers were not and are not immune to being put to sleep, both by the political actors and by the judge. The first question raised by the constituent function in Black Africa is therefore that of its reality, its effectiveness. In other words, it is a question of knowing whether judges really build constitutions in Africa, the question of their empowerment being irrelevant since it is regulated by the texts or constitutional jurisprudence. This first question is joined by a second. Logically, one can ask whether the jurisdictional revision of the constitution in Black Africa has particular characteristics, i.e. specific to the Francophone space. Interpreting a constitution or regulating institutions is not the privilege of African judges alone. The constituent function is exercised elsewhere, at least in all civil law systems with a constitutional jurisdiction. In Africa, therefore, the exercise of the constituent function should be different from others. To put it more clearly, the constituent function must be singular.The present thesis aims to systematise the constituent function of the Afri
Keywords: African Research